Total physical response method to enhance listening skill. - Freire Carrillo, Sofía Fernanda (2024)
Continuous language learning, especially in English, is a necessity in our globalized world. Therefore, teachers of this subject must constantly update their teaching methods. However, there is a pressing need for more effective strategies in the classroom, a lack of adequate evaluation processes, and a scarcity of knowledge about the Total Physical Response (TPR) Method. This problem limits its use in teaching English, particularly in developing listening comprehension. This research was developed among students at the first parallel level, "F2," of the National University of Chimborazo. It analyzes the TPR method for teaching English to improve listening skills. The methodology used is descriptive and mixed. The results obtained have led to the development of a proposal that focuses on enhancing students' listening comprehension through the innovative use of the TPR method. Therefore, we propose the implementation of TPR as a novel strategy that can significantly enhance students' English listening skills. The findings indicate that current methodological strategies for developing listening comprehension could be more effective and that the TPR method needs to be more widely applied. Therefore, it is recommended to incorporate this approach during the learning process to improve the teaching of English in listening skills.